Child-Friendly Islamic Education Based on Local Wisdom - Sayyi, Ach.; Fithriyah, Imaniyatul; Al-Manduriy, Shahibul Muttaqien (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study aims to analyze the implementation of child-friendly Islamic education based on religious moderation at MAN 2 Pamekasan, focusing on learning strategies, the integration of local wisdom, and the reinforcement of love and tolerance values. Employing a qualitative case study with an ethnographic orientation, the researcher collected data through participatory observation, semi-structured interviews, document analysis, and focus group discussions (FGD). The ethnographic lens allowed the researcher to capture the cultural nuances, lived experiences, and symbolic practices that shape the madrasah’s educational environment. Findings indicate that MAN 2 Pamekasan successfully creates a safe, inclusive, and participatory learning climate by combining teacher role modeling, religious habituation, and the integration of Madurese local wisdom, particularly the buppa’-babu’-guruh-rato philosophy. These values are embedded into the curriculum, which emphasizes active student participation in dialogue, reflective learning, and collective practices, resulting in the internalization of moderation, love, and tolerance in everyday life. The findings resonate with classical theories of al-Ghazali on adab and Ibn Khaldun on social solidarity, modern theories of Piaget and Vygotsky on cognitive and social interaction, and contemporary frameworks (2023–2025) on child-friendly learning and the Islamic pedagogy of care. This study contributes theoretically to the discourse on Islamic education based on moderation and practically to the prevention of radicalism and intolerance, positioning MAN 2 Pamekasan as a replicable model of ethnographically grounded, child-friendly Islamic education.